WELFARE PSYCHOLOGICAL WELL-BEING OF RETIRED ELEMENTARY SCHOOL TEACHERS: IDENTIFYING SYMPTOMS AND SOLUTIONS OF POST POWER SYNDROME – CASE REPORT - Anggriani, Dina Delvin; Masrochanah, Siti; Putri, Cyntia Hemas Febrina; Pertiwi, Berliana Noviasih; Istiqomah, Ratri (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: Post Power Syndrome is a psychological condition often experienced by individuals who lose an important social position or status, particularly in retirees who previously held leadership roles. The drastic change from being active and respected to being retired can lead to feelings of loss of identity and meaning in life, often resulting in psychological symptoms such as depression and anxiety. This study aims to understand the dynamics of Post Power Syndrome in a retired female teacher and the factors influencing her ability to adapt to post-retirement life. Methods: This research uses a qualitative case study approach. Data was collected through in-depth interviews, participant observation, and document analysis. The Pattern Matching technique was used to analyze the data and identify main patterns and themes related to the experience of Post Power Syndrome. Results: The study subject exhibited emotional symptoms such as sadness, anxiety, and feelings of isolation, as well as behavioral changes including difficulty sleeping and altered eating patterns. Although the subject managed to fill her free time with new activities like gardening, symptoms of Post Power Syndrome remained evident in her stories and behavior. Discuss: Emotional distress leads to maladaptive coping mechanisms, such as substitutive reactions and overthinking memories. This study highlights the importance of direct observation and interviews to accurately analyse behavioural symptoms. Direct field observations and interviews are essential in understanding the behavioural changes exhibited by retired teachers experiencing post-power syndrome. Conclusion: Post-Power Syndrome can affect individuals' emotional well-being and behavior after retirement. Social support and psychosocial intervention strategies are crucial for helping retirees manage life changes. This research also provides insights for educators and psychologists in offering more effective support to retired teachers.   Keywords: post-power syndrome, retirement, teacher.